Existence of Solutions for Quasilinear Weakly Coercive Elliptic Variational Inequalities (Journal of Partial Differential Equations, 1995)
In this note we give an existence result to a class of variational inequalities associated with quasilinear elliptic operators of second order with lower order terms. We prove “a priori” estimate by an extension of the truncation method to the nonlinear case.
Keywords: Weakly coercive; variational inequality; truncation method; existence; closed convex set